2017
DOI: 10.4103/ijciis.ijciis_108_16
|View full text |Cite
|
Sign up to set email alerts
|

Otorhinolaryngological manifestations in head trauma: A prospective study of the epidemiology, clinical presentations, management, and outcomes

Abstract: Background:Otorhinolaryngological injuries following head trauma may be missed, overlooked, or forgotten in the acute phase resulting in worsened management outcomes. This study aims to report the epidemiology, clinical presentations, management, and outcomes of otorhinolaryngological injuries in head trauma with a view to creating awareness for early recognition and prompt treatment.Patients and Methods:Head injured patients consecutively presenting over a 5-year period were prospectively studied for age, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…21 Males were predominantly involved according to Adoga and colleagues. 22 We report comparable results since young males are more vulnerable to trauma due to their outdoor activities and occupational exposure. Hardman et al found that TBI was most common in young adults aged 15 -24 years.…”
Section: Discussionsupporting
confidence: 65%
“…21 Males were predominantly involved according to Adoga and colleagues. 22 We report comparable results since young males are more vulnerable to trauma due to their outdoor activities and occupational exposure. Hardman et al found that TBI was most common in young adults aged 15 -24 years.…”
Section: Discussionsupporting
confidence: 65%
“…10 Adoga et al, in a study found that common otorhinolaryngological presentations of CSF leaks were rhinorrhea followed by otorrhea. 15 Contrary to this, Yellinek and his colleagues in their study reported that otorrhea is more frequent then rhinorrhea in cases of CSF leak secondary to traumatic brain injury. 19 In our study, 22 patients had CSF leaks out of total 422 patients i.e.…”
Section: Discussionmentioning
confidence: 87%
“…14 CSF traumatic leaks occur commonly in young males and complicate 2% of all head injuries, and 12% to 30% of all basilar skull fractures. 11 Adoga and colleagues 15 , in their study on otorhinolaryngological manifestations in head trauma found that majority of patients with head injury were male patients and the most affected population was below 40 years. 15 We report comparable results, as in our study also, most of the patients with head trauma (79.6%) and CSF leak (82%; 18/22) were male.…”
Section: Discussionmentioning
confidence: 99%
“…The preponderance of males and young people in head and neck and orofacial trauma is well documented and attributed to traditional behavioral and occupational patterns of these groups that predispose them to injury. 12 , 13 , 19 , 21 - 23 …”
Section: Discussionmentioning
confidence: 99%